Traveling questions: uncertainty and nonknowledge as vehicles of translation in genetic research participation. Issue 4 (1st October 2016) - Hoeyer, Klaus
Abstract : In this paper, I argue that uncertainty and nonknowledge, and not just research results, can be important vehicles of translation through which genetic research participation comes to affect the lives of research participants. Based on interviews with participants in a genetic research project, I outline epistemic, emotional, relational and moral implications of research participation. Many of them resemble what the literature has described as the social implications of genetic counseling, but here they stem from interaction with knowledge-in-the-making or what I simply call nonknowledge. While policies aimed at stimulating translation from bench to bedside tend to build on the assumption that research only works when knowledge translates into technological ability and creates utility, I suggest acknowledging that research has implications long before any clinical applications are at hand. Research questions, and not just results, may serve as a generative form of knowledge that can travel as fast as any answer.